Reactive Oxygen Species Imaging in U937 Cells - Prasad, Ankush; Sedlářová, Michaela; Balukova, Anastasiia; Ovsii, Alina; Rác, Marek; Křupka, Michal; Kasai, Shigenobu; Pospíšil, Pavel (Frontiers in Physiology, 2020)
The U937 cell culture is a pro-monocytic, human histiocytic lymphoma cell line. These monocytes can differentiate into either macrophages or dendritic cells (antigen-presenting cells) depending on the initiators. The U937 cells activated in the presence of phorbol 12-myristate 13-acetate (PMA) change their morphology into macrophage-like cells creating pseudopodia and adhering generously. Macrophages are known to produce reactive oxygen species (ROS) mostly during phagocytosis of foreign particles, an important non-specific immune response. Recently, we have focused on the role of hydroxyl radical (HO●) and provide evidence on its importance for differentiation in U937 cells. Based on electron paramagnetic resonance (EPR) spectroscopy combined with confocal laser scanning microscopy (CLSM), formation of HO● was confirmed within the cells undergoing differentiation and/or apoptosis during the PMA treatment. This study aims to increase our knowledge of ROS metabolism in model cell lines used in human research.